Utilization of Wokwi Technology as a Modern Electronics Learning Media - Darmaji, Darmaji; Jamlan, Muain; Nkweke, Obinna C; Boglou, A. K.; Baharin, Zain Hazmi Zain (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to develop Wokwi simulation-based teaching materials using the 4D model (Define, Design, Develop, Disseminate) to improve the understanding and science process skills of physics education students. Methodology: The Define stage identifies learning needs, while the Design stage designs interactive and easy-to-use teaching materials. In the Develop stage, the prototype is tested to assess the effectiveness of the simulation, resulting in a significant increase in students' understanding of basic concepts. This study involved 50 5th semester students at Jambi University, using questionnaires and observation sheets as instruments. Main Findings: The results of the analysis showed that the majority of students had science process skills in the "Good" category (44%) with an average score of 78.4, while the response to the use of Wokwi was mostly in the "Quite Good" category (40%) with an average score of 65.3. The correlation test revealed a significant positive relationship (r = 0.532; p = 0.001) between the use of Wokwi and science process skills. Novelty/Originality of this study: The novelty of this research is presenting innovation in electronics learning through the integration of Wokwi technology, which allows interactive and practical circuit simulation for students without the need for physical hardware. This study offers a new perspective in the development of technology-based digital learning media by utilizing Wokwi, which is designed to improve students' conceptual understanding and technical skills in electronics.